DESCRIPTION OF CULTURAL INTELLIGENCE OF MEDICAL STUDENTS - Putri, Shylva Budiani; Meidianawaty, Raden Vivi; Permatasari, Tissa Octavira (Universitas Gadjah Mada, 2025)
Background: Cultural intelligence is the ability of individuals to adapt to different cultural situations based on various aspects, namely metacognitive, cognitive, motivational, and behavioral. Awareness of understanding about cultural intelligence makes medical students more able to adjust to interacting with or being in a different cultural environment. Aims: To identify the cultural intelligence of medical students at Swadaya Gunung Jati University based on metacognitive, cognitive, motivational, and behavioral aspects. Methods: This study used an observational descriptive method with a cross-sectional design and consecutive sampling methods. Data were obtained using the Cultural Intelligence Scale questionnaire based on four aspects: metacognitive, cognitive, motivation, and behavior. Result: Based on 167 medical students, from 4 aspects of cultural intelligence, most respondents have high metacognitive intelligence, moderate cognitive, high motivation, and moderate behavior. In clinical rotation students, the majority have high metacognitive intelligence, high cognitive, moderate motivation, and moderate behavior. The majority of academic students have high metacognitive intelligence, moderate cognitive abilities, high motivation, and moderate behavior. Conclusion: The majority of respondents have moderate cultural intelligence, with the best intelligence aspect being metacognitive intelligence. Cultural intelligence can be influenced by the learning process, environment, learning style, or information absorption process, and social skills and cultural intelligence can be improved by training, experience, and education.